KEBIJAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PORNOGRAFI ANAK PADA DUNIA MAYA - Farah Diba Batubara; Alvi Syahrin; Mahmud Mulyadi; Edy Ikhsan (Universitas Sumatera Utara, 2018)
ABSTRACT Advances in technology and the characteristics of the internet that is free resulted in the large number of children become victims of child pornography crimes. Child pornography continues to increase every year, even with the existing regulations worldwide including Indonesia still has not been able to reduce or eradicate these crimes. Problems that can be diuarikan IE, please note the development of the criminal offence of child pornography in Indonesia, the implementation of the sanctions for the perpetrators of the crime of child pornography in cyberspace in Indonesia, and the criminal law policy will come against the crime of child pornography in cyberspace in Indonesia. The research method used is the juridical normative with secondary data analyses in the form of primary legal materials and legal materials, skunder comparative juridical review to do a comparison against the setting of child crime in some countries. The data collection method used is the study of librarianship and the method of data analysis used the methods of normative qualitative analysis. Legal developments occur starting from 1946 until 2015, which is experiencing the development of good elements in certain jurisdictions as well as the criminal sanctions imposed on perpetrators of acts of pidananya. However, the current regulations are considered still hasn't been able to catch the perpetrators of child pornography in cyberspace. If seen on the application of the law, the law enforcement of criminal penalty nonetheless is in compliance as exists in laws – an invitation on perpetrators of child pornography. In penal policy that will come then to note is the study of criminal law policy regarding the anniversary of the crime of child pornography and need harmonization and connectivity in the regulations of the CRIMINAL CODE and regulations outside the PENAL CODE. Penal policy, is expected to accommodate international value adaptively adjusted with the values of Pancasila. Keywords: penal policy, child pornography, internet.